A Development of Teaching resources: Based on West Java Ethnomathematics for Grade 7 Middle School students - Syifa Fauziah; Sirojudin Wahid (Ilmu Inovasi Nusantara, 2021)
This study aims to develop teaching resources based on West Java ethnomathematics, while the teaching resources developed are learning modules. The method used in this study is R&D method using the ADDIE development steps (Analysis, Design, Development, Implementation and Evaluation). The finished product is validated by 2 experts. each expert is given an assessment sheet regarding the learning module. The first expert assesses the suitability of the material used in the module, while the second expert assesses the feasibility of the module from the appearance aspect. The results of the validation by the first expert stated that the module was included in the